2011
DOI: 10.1016/j.bbrc.2011.07.109
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor REIC/Dkk-3 interacts with the dynein light chain, Tctex-1

Abstract: Running title: REIC/Dkk-3 interacts with Tctex-1. The link between REIC/Dkk-3 and Tctex-1 may be of significance for understanding the molecular functions of the proteins in ER stress signaling and intracellular dynein motor dynamics, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 23 publications
3
23
1
Order By: Relevance
“…It is also reported that the adenovirusmediated expression of the REIC/Dkk-3 gene efficiently induces endoplasmic reticulum (ER) stress-mediated apoptosis in a manner specific to cancer cells (4,20,21). The present study demonstrated that Ad-REIC treatment induces significant apoptosis in human prostate cancer cells and hepatoma cell lines; however, Ad-REIC treatment does not induce apoptosis in normal human cells.…”
Section: Discussioncontrasting
confidence: 57%
“…It is also reported that the adenovirusmediated expression of the REIC/Dkk-3 gene efficiently induces endoplasmic reticulum (ER) stress-mediated apoptosis in a manner specific to cancer cells (4,20,21). The present study demonstrated that Ad-REIC treatment induces significant apoptosis in human prostate cancer cells and hepatoma cell lines; however, Ad-REIC treatment does not induce apoptosis in normal human cells.…”
Section: Discussioncontrasting
confidence: 57%
“…The binding partner of intracellular REIC/Dkk-3 protein has been investigated by several previous studies. It has been reported that Dkk-3 binds to other proteins, such as Kremen1/2 (28,29), β-TrCP (30) and TcTex-1 (31), and that these interactions occur in the cytoplasm. These proteins include substantial molecules that significantly affect and modify intracellular signaling pathways, including the Wnt and TGF-β (16,32).…”
Section: Physiological Functions Of Reic/dkk-3mentioning
confidence: 99%
“…Dkk-1, -2 and -4 inhibit Wnt/b-catenin signals by binding to LRP5/6 (Niehrs, 2006), but Dkk-3 does not bind to these proteins directly (Mao and Niehrs, 2003;Mao et al, 2001). Instead, Dkk-3 has been reported to affect Wnt signalling through binding other proteins, namely Kremen1/2 (Nakamura and Hackam, 2010), b-TrcP (Lee et al, 2009) and TcTex-1 (Ochiai et al, 2011). However, Dkk-3 is a secreted protein and the relevance of these interactions, which take place in the cytoplasm, to the function of endogenous Dkk-3 remains unclear.…”
Section: Introductionmentioning
confidence: 99%